The effects of heritage multilingualism on foreign language learning: a comparison of children with typical language development and developmental language disorder - Tribushinina, Elena; Boz, Betül (Frontiers in Psychology, 2025)
IntroductionBoth multilingualism and developmental language disorder (DLD) may be associated with inferior performance in the majority language, albeit for different reasons. At the same time, there is a growing body of evidence that multilingualism may have a positive effect on foreign language performance. This study tests the hypothesis that the positive effects of multilingualism on foreign language learning may be smaller in children with DLD compared to their multilingual peers with typical language development.MethodsIn a 2 × 2 design, we compare the effects of multilingualism and DLD on English as a foreign language performance and majority language performance of multilinguals and monolinguals with and without DLD. The participants were primary school children (aged 9–13) acquiring Dutch as the majority language and learning English as a school subject. English skills were measured with a vocabulary test, a grammar test and the Multilingual Assessment Instrument for Narratives (MAIN). Dutch skills were assessed with the Litmus Sentence Repetition Task and the MAIN task. The MAIN narratives in both languages were analyzed for fluency, lexical diversity, syntactic complexity and grammatical accuracy. The control variables included age, working memory, declarative memory, procedural memory and (for English) amount of extracurricular exposure and length of instruction. Data were analyzed by means of multilevel linear regression.ResultsThe results demonstrate that both multilingualism and DLD were associated with lower scores on the Dutch Sentence Repetition Task and lower grammatical accuracy of narratives. In English, the multilinguals outperformed monolinguals on all measures, except grammatical accuracy of narratives, and the interactions between Background and Group were not significant. Another strong predictor of EFL performance, along with the multilingual status, was extracurricular exposure to English.